Satisfaction of Students’ Technology, Cognitive and Content Knowledge (TSCCK) in the cloud - Qiong Wu; Thanin Ratanaolarn (My University, 2023)
The TSCCK model includes Student Cognitive Knowledge (SCK) which refers to the concept of cognitive load involved in cognitive load theory and how teachers should adopt appropriate instruction design to promote students' learning. Student Technology Knowledge (STK) refers to students’ knowledge of traditional and new technologies that can be integrated into learning. Student Content Knowledge (SK) refers to any subject-related knowledge that a student should learn. Firstly, we randomly selected 90 students from a total of 115 students (simple random sampling) majoring in E-commerce to participate in the experiment. Questionnaire (5-point Likert scale) to understand the current status of technology, cognitive, and content knowledge of vocational college students. Secondly, to verify the TSCCK model, experts were invited to test and evaluate the model's reliability and validity, the scores of the TSCCK model were evaluated by five experts through a questionnaire (5-point Likert scale), in which the maximum mean score was 4.8, and the minimum mean score was 4.6. As can be seen from the table, the overall mean was 4.6, and the SD was 0.4. Therefore, experts agreed with the core idea of the TSCCK model. This means that the TSCCK model's three basic ideas have been recognized by experts. Thirdly, to find the satisfaction level of the vocational students’ technology, cognitive, and content knowledge, under the TSCCK model with a cloud for vocational students, 10 students were taught using the TSCCK model with a cloud; and they were assessed by an E-commerce test and WP scale, with criteria of 80% for the achievement test and the low cognitive load (WP scale) level. The result from the E-commerce test score were passed (criteria: 80%) and the WP scale scores were low among the students, and the questionnaire also showed a satisfactory level.
Keywords: Online and Blended Learning; Visual and Cognitive Learning Processes; Innovative Teaching and Learning Methods